1996
DOI: 10.7146/kok.v23i80.20709
|View full text |Cite
|
Sign up to set email alerts
|

Unhooked

Abstract: Verner Møller, Jørgen Povlsen og Kurt Lüders (red.): Hooked. Om vanvid  og æstetik i sport og kropskultur

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Moreover, in vivo experiments carried out by overexpressing the native mazF gene indicated that the RNA cleavage by MazF occurs not only at 5 0 -NAC-3 0 sites [18,21], thus further supporting our view that the intrinsic activity of MazF is subject to additional controls. Possibly, the in vivo function of MazF is determined by its interaction with particular host factors (e.g., components of the translation machinery) in response to specific physiological stimuli, as previously suggested [18]. However, the relaxed substrate specificity of MazF and the fact that cleavage occurs in a ribosome-independent manner suggest that the ribonuclease activity of MazF may not be restricted to targeting messenger RNA, but rather involves the regulation of a larger panel of RNA-dependent cellular processes.…”
Section: Rna Cleavage Assayssupporting
confidence: 79%
See 4 more Smart Citations
“…Moreover, in vivo experiments carried out by overexpressing the native mazF gene indicated that the RNA cleavage by MazF occurs not only at 5 0 -NAC-3 0 sites [18,21], thus further supporting our view that the intrinsic activity of MazF is subject to additional controls. Possibly, the in vivo function of MazF is determined by its interaction with particular host factors (e.g., components of the translation machinery) in response to specific physiological stimuli, as previously suggested [18]. However, the relaxed substrate specificity of MazF and the fact that cleavage occurs in a ribosome-independent manner suggest that the ribonuclease activity of MazF may not be restricted to targeting messenger RNA, but rather involves the regulation of a larger panel of RNA-dependent cellular processes.…”
Section: Rna Cleavage Assayssupporting
confidence: 79%
“…In contrast, three lines of evidence argue in favor of our observations: (i) all the 5 0 -(U/A)AC-3 0 sites present in TAR, CopA or CopT RNAs were cut by MazF, with no exception (this work; Fig. 3B); (ii) 5 0 -AAC-3 0 present in the E. coli tmRNA was a strong cleavage site for MazF in vivo [18]; and (iii) although presented as an exception rather than a rule, Zhang et al [21] also show that the lacZ mRNA is cleaved by MazF between the U and A residues in a 5 0 -UAC-3 0 site. However, the reasons for the discrepancy between the work reported here and that of Zhang and co-workers are unclear.…”
Section: Rna Cleavage Assaysmentioning
confidence: 47%
See 3 more Smart Citations